2019
DOI: 10.13189/ujps.2019.070301
|View full text |Cite
|
Sign up to set email alerts
|

Fruits Morphological Qualitative Traits, Biochemical Components and Pungency Strength of Spicy Pepper from Maleh Valley in Morocco

Abstract: Phenotypic diversity, biochemical components and pungency strength were assessed for eighteen spicy pepper accessions from Maleh valley in Morocco. Six plant samples were randomly collected in farmers' field across three target localities during 2015 growing season. Eight fruits from each sampled plant were characterized using eight phenotypic qualitative traits and biochemical components. Results revealed a wider genetic variability within accessions (52%) than among accessions (43%) and among sites (5%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
2
1
Order By: Relevance
“…The mean carbohydrate contents reported by different workers (Benbrahim et al, 2019;Plaza et al, 2021) agree with the values reported in the present study. Dissimilar results were reported by Liberal et al (2021) and Alghamdi et al (2014).…”
Section: Chemical Determinationssupporting
confidence: 92%
See 1 more Smart Citation
“…The mean carbohydrate contents reported by different workers (Benbrahim et al, 2019;Plaza et al, 2021) agree with the values reported in the present study. Dissimilar results were reported by Liberal et al (2021) and Alghamdi et al (2014).…”
Section: Chemical Determinationssupporting
confidence: 92%
“…Among leguminous species, lentil (Lens culinaris Med) is an ancient crop of classical Mediterranean civilization (Karakoy et al, 2012) consumed in appreciable amounts in Middle East countries (Bamdad et al, 2009;Ying et al, 2017). Nowadays, lentil is an important pulse crop which is cultivated worldwide for human food security especially in developing countries (Gupta et al, 2021;Benbrahim et al, 2019;Moldovan et al, 2015). Interest in the production and use of lentil in food formulation and preparation has grown in the last decades due to their high nutritional value and fast cooking times (Barbana & Boye, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to Benbrahim et al (2019), the mean value of TPC for Maleh spicy pepper was determined as 73.28 mg GAE/100 g. The maximal value, in this case, was 223.5 mg GAE/100 g, which was less than in our study. As reported by Bertão et al (2016), TPC in ethanol extracts of C. annuum was 341.78 mg GAE/g, of C. baccatum 156.76 mg GAE/g, and of C. chinense 107.98 mg GAE/g.…”
Section: Resultscontrasting
confidence: 67%
“…It is crucial to any crop improvement to choose desirable parent material, but it is a quite challenging task for crop breeders. The genetic divergence of any crop is regarded as a key component in achieving heterotic response in the F1 generation, and a large range of diversity exists in segregating generations (Arunanchalam, 1981;Benbrahim et al, 2019). The estimation of genetic diversity is critical for identifying genetically different genotypes (Mukhopadhyay and Bhattacharjee, 2016).…”
Section: Cluster Analysismentioning
confidence: 99%